A recorribilidade das decisões arbitrais em matéria de arbitragem administrativa voluntária - Marques, Mafalda Magalhães Roque Roda (2021)
Despite having appeared as an alternative mechanism for resolving disputes purely under private law, it is certain that arbitration has been increasingly gaining more space and prominence in the settlement of legal-administrative disputes. However, not so certain is that to it corresponds a regulation, under the CPTA, worthy of its current status; in fact, despite its growth, the regime applicable to voluntary administrative arbitration, provided for in Articles 180 et. thereafter of the CPTA, since its emergence, has been, to a great extent, and almost exclusively, dependent on what is stipulated in the LAV. An example of this was the regime applicable to the appeals of administrative arbitral awards, which, until the entry into force of the amendments introduced by Law 118/2019 of 17.09 to the CPTA, respected only the provisions of Article 39(4) of the LAV – according to such article, an appeal of arbitration decisions could only take place if the parties so agreed to in the arbitration agreement. Through the above-mentioned Law, was therefore determined the addition of the brand-new Article 185a of the CPTA, which expressly enshrined three possibilities for appeal against voluntary administrative arbitration decisions: constitutionality appeal, appeal for uniformity of jurisprudence and, finally, review appeal. In view of such innovation, the aim of this study was to achieve two distinct, albeit invariably complementary, goals. Firstly, to contribute to a clarification of such innovative possibilities, currently guaranteed by Article 185a of the CPTA (and, thus, for its operationalization), through an in-depth analysis of each of those, taking in due consideration the regimes applicable to the same types of appeals in other jurisdictions – not only in administrative litigation, but also, in what concerns certain aspects, in civil proceedings and in tax arbitration – which are currently much more developed and scrutinized, both by Jurisprudence and by the Doctrine. Secondly, to ascertain the adequacy and dignity of such solutions to the means of settling disputes to which they relate, answering, thereby, the question to know if this is the best appeal regime to be adopted within voluntary administrative arbitration.